COMPARATIVE ASSESSMENT OF THE EFFICACY AND MORPHOLOGICAL TOLERABILITY OF LOCAL HEMOSTATIC AGENTS IN LIVER INJURIES - Khamdamov, B.Z.; Ganzhiev, F.Kh.; Bobokulova, Sh.A.; Achilova, O.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction. Traumatic liver injuries are accompanied by a high risk of life-threatening complications, primarily massive bleeding. A critical link in a successful surgical intervention is the choice of an adequate local hemostatic agent, which should take into account not only hemostatic properties, but also tissue compatibility. Purpose. To conduct a comparative assessment of hemostatic efficacy, operational suitability and morphological tolerability of various local hemostatic agents in a clinical and experimental model of liver injury. Material and methods. The study included 80 laboratory animals (Wistar rats) with blunt and cut liver injury simulations. Surgicel®, TachoSil®, Biatravm® and BloodSTOP IX were evaluated. Hemostasis time, blood loss, the need for repeated application, as well as histological analysis on days 3, 7 and 14 were recorded. The clinical part included 44 patients divided into two groups depending on the use of the algorithm for choosing a hemostatic agent. Results. The best indicators of hemostasis time and blood loss volume were recorded with the use of BloodSTOP IX. The drug provided high adhesion, did not require compression and was accompanied by a minimal inflammatory reaction and the absence of bile impregnation. In the clinical group, where the selection algorithm was used, there was a reduction in the duration of bleeding by more than 2 times and a decrease in the frequency of repeated application. Conclusion. BloodSTOP IX demonstrated the best combination of hemostatic activity, technical convenience, and morphological biocompatibility. The data obtained confirm its preference for parenchymal liver damage, and the proposed algorithm for choosing the drug increases the reproducibility and safety of surgery.